Database of satellite polarimetry - Zaitsev, S.V.; Rosenbush, V.K.; Kiselev, N.N. (Advances in Astronomy and Space Physics, 2013)
We present the electronic database (EAR-SA-COMPIL-3-SATPOL-V1.0, NASA Planetary Data System), involving 2355 published and 105 unpublished results in planetary satellite polarimetry. The database contains 2460 measurements of linear polarization of planetary satellites, including fifteen measurements of polarization for the Martian satellites (Phobos and Deimos), 2318 measurements for five Jovian satellites (Io, Europa, Ganymede, Callisto, and Himalia), 127 measurements for two Saturnian satellites (Titan and Iapetus). Broad-band measurements within the spectral region 233-850 nm are presented. The range of phase angles is 0.1°-154° . The geometric conditions of observations (phase angle, planetographic longitude and latitude of the target disk centre seen by the observer, and position angle of the scattering plane) are calculated for given moments of time according to the JPL Horizons ephemeris system. We have compiled nineteen references to the published papers and some unpublished sources. The data are provided in a tabular ASCII format. The database can be used as the observational basis for detailed theoretical modelling, interpretation of the phase-angle and spectral dependence of polarization, and for selecting future space-mission targets.